2005
DOI: 10.1139/l05-043
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the impact of corrosion control measures on tap drinking water of the Greater Vancouver Regional District

Abstract: A study on the quality of water distributed within the Greater Vancouver Regional District (GVRD) was carried out to evaluate the effectiveness of previously implemented corrosion controls. In addition, the effect of temperature fluctuations was investigated to determine if it influenced the efficacy of the control measures. The GVRD was divided into four distribution areas. The Capilano water had no corrosion control treatment. Seymour, Coquitlam, and Newton waters were treated with soda ash, resulting in a p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…However, small variations in pH levels did not affect the concentrations of lead present in the samples taken at the tap suggesting corrosion control did not affect the levels of lead found (26). Similarly, Deshommes et al, found extreme lead concentrations up to 2640 times greater than the MAC after an 8-hour stagnation period along with a sample reaching 186 times greater than the MAC after a 5-minute flush in buildings serviced by lead plumbing and piping along with corrosive water (11).…”
Section: Relationship Between Plumbing Water Quality and Lead Concen...mentioning
confidence: 93%
See 4 more Smart Citations
“…However, small variations in pH levels did not affect the concentrations of lead present in the samples taken at the tap suggesting corrosion control did not affect the levels of lead found (26). Similarly, Deshommes et al, found extreme lead concentrations up to 2640 times greater than the MAC after an 8-hour stagnation period along with a sample reaching 186 times greater than the MAC after a 5-minute flush in buildings serviced by lead plumbing and piping along with corrosive water (11).…”
Section: Relationship Between Plumbing Water Quality and Lead Concen...mentioning
confidence: 93%
“…The highest amount of lead was found in the first and second samples after a cold-water flush at the tap compared to samples at the source of the water in each region (26). These results are indicative that corrosion of household plumbing during the delivery of water contributed to the significant increases in levels of lead and impacted the water quality (26).…”
Section: Relationship Between Plumbing Water Quality and Lead Concen...mentioning
confidence: 94%
See 3 more Smart Citations